Penerapan Etika Bisnis Islam Dalam Produksi Budidaya Jamur Tiram Putih “Sari Kayu” Kecamatan Jetis Kabupaten Mojokerto - Ali Masduqie, Muhammad Hamdan; Shafira Hafatareta, Shalla; Shinta Hardiyanti, Istiqom; Afri Suhairi Panjaitan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to answer the problem formulation in this research, namely how the production process of white oyster mushroom cultivation "Sari Kayu", and how to apply Islamic business ethics in the production of white oyster mushroom cultivation "Sari Kayu", Jetis District, Mojokerto Regency. The research methodology used in the research conducted on the cultivation of white oyster mushrooms “Sari Kayu” uses a descriptive qualitative approach. As for this study using field research methods and based on primary data and secondary data. The technique of collecting data is by means of observation, interviews, and documentation. The research results obtained from this research are that the production process is in accordance with the production process in Islam, and the overall production activity has met the principles of Islamic business ethics and applies the principles of production in Islamic Economics